Web-Based Career Path Model for Human Resource Management - Chin Neoh, Siew; Jun Tan, Choo; Seera, Manjeevan; Kiong Loo, Chu (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2016)
Career path modeling and management are essential for building appropriate business strategies to attract and maintain valuable human assets in an organization. The increase of data volume due to globalized employment has increased the challenge to utilize scattered and abundant data which are collected from time to time. In order to ensure efficient top to bottom communication in an organization, this paper proposes a web-based software tool for career path modeling. It aims to assist employees from different departments to seek advice in terms of their career advancement opportunities, and support managerial decision from the human resource professionals. The proposed model is developed with the consideration of several aspects, i.e., change of job position, department, gender, attended training courses, available mentor, as well as professional and academic qualifications. The concept of cloud computing is adopted to ensure the accessibility of the model from different web-browsers so that employees have the flexibility to obtain career advancement information anytime and anywhere.